2020
DOI: 10.1002/cche.10359
|View full text |Cite
|
Sign up to set email alerts
|

Functional and nutritional characterization of in vitro enzymatic hydrolyzed millets proteins

Abstract: Background and objectives Millets protein has been reported to possess potential bioactive peptides. In current study, effects of in vitro enzymatic hydrolysis on physicochemical and functional properties of pearl millet (PM), finger millet (FM), and green sorghum millet (GSM) protein were assessed. Findings Millets protein isolates were in vitro enzymatically hydrolyzed using pepsin and pancreatin. Essential amino acids such as leucine and threonine content were increased and found to be higher in PM protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Agrawal et al (2020) used pancreatin and pepsin to develop various hydrolysed millet protein isolates. In particular, the pearl millet protein hydrolysate has a high profile of essential amino acids like threonine and leucine, 33.19 and 128.04 mg/g, respectively.…”
Section: Millets Based Technologiesmentioning
confidence: 99%
“…Agrawal et al (2020) used pancreatin and pepsin to develop various hydrolysed millet protein isolates. In particular, the pearl millet protein hydrolysate has a high profile of essential amino acids like threonine and leucine, 33.19 and 128.04 mg/g, respectively.…”
Section: Millets Based Technologiesmentioning
confidence: 99%
“…The hydrolyzed protein fractions have relatively lower molecular mass, better bioavailability, and improved quality of functional properties than the native proteins such as emulsification, water‐ and fat‐holding capacities, foaming ability, gelation & solubility. Furthermore, they tailor the functional properties of proteins to meet some specific needs of distinct food formulations (Agrawal et al, 2020; Kamara et al, 2010).…”
Section: Biological Processing Techniquesmentioning
confidence: 99%
“…Furthermore, release of bound bioactive components (Adeleke et al, 2017) as been associated with germination, fermentation and other enzymatic treatments. Synthesis of microbial enzymes during fermentation such as cellulases, xylanases, pectinases, β‐glucosidase, β‐galactosidase, α‐amylases, and β‐xylosidase also causes desirable changes in the bioactive composition, antioxidant activity, and digestibility of the nutrients (Agrawal et al, 2020; Purewal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have certified that a series of hydrolysates from plant protein, such as soybean, mung bean, black bean, rice, and millet protein hydrolysates, have shown beneficial health effects such as antioxidant, anti‐hypertensive, antibacterial, antifatigue, and immunomodulatory activities (Liu et al., 2018; Xia et al., 2020; Zheng et al., 2019). Moreover, many researchers demonstrated that the hydrolysates and bioactive polypeptides can be used as nutritional resources in the functional food industry (Agrawal et al., 2020; Chang et al, 2020; Yu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%